TINGKAT PENDAPATAN PENGRAJIN BORDIR KHAS ACEH DI GAMPONG DAYAH DABOH KECAMATAN MONTASIK KABUPATEN ACEH BESAR - Muyassirati, Nasywa; Abdi, Abdul Wahab; Diah, Husna (Universitas Syiah Kuala, 2025)
Embroidery is one of the SMEs that is being developed in Aceh Besar. The income level of embroidery craftsmen in each region is of course different. This research aims to find out how the income level of embroidery craftsmen in Gampong Dayah Daboh, Montasik District, Aceh Besar District, the term embroidery is often also referred to as sulam or the art of decorating cloth or clothing materials using needle and thread. The population in this study are women who are members of several groups of embroidery business craftsmen in Gampong Dayah Daboh with a total of 30 active workers. Data collection techniques using questionnaires and data analysis techniques using simple statistical formulas. Data processing in this study uses descriptive statistical formulas. Based on the results of data processing, it can be concluded that those who strongly agree are 49.6%, agree 30.4%, disagree 7.6%, disagree 12.4%, and strongly disagree 0%. Based on these results, the overall level of income for embroidery craftsmen in Gampong Dayah Daboh, Montasik District, Aceh Besar District, is Rp.2,500,000, based on the BPS classification, this income is categorized in the high income category. Thus it can be concluded that Gampong Dayah Daboh embroidery craftsmen have high economic capacity.